(untitled) (Journal of the Entomological Research Society, 2023)
The present study provides faunal data for Turkish Black flies (Simuliidae, Diptera) from the Central and Western Mediterranean Region in Türkiye. Among the specimens collected from 221 different running water sites, 17 species in 3 genera and 5 subgenera were identified. Two species, Simulium (Nevermannia) ibleum (Rivosecchi 1966) and Simulium (Nevermannia) brevidens (Rubtsov 1956), were recorded for the first time from Türkiye, and 5 additional species were reported from the study area for the first time. The morphological identifications were tested by phylogenetic analyzes using mitochondrial cytochrome oxidase I (COI) barcode sequences. The COI analysis results overlapped with the morphotaxonomic identification results for eight of the 15 species. The first genetic data of 4 species (for World) and 5 species (from Türkiye) were stored in GenBank (NCBI).